TACKLING THE NIGERIA SECURITY CHALLENGES: THE ISLAMIC PANACEA - Elesin ʻAbdulwahab Muhammad Jāmiʻu (European Scientific Journal, ESJ, 2013)
Nigeria as a country, due to rampant corruption and immoralities, is currently witnessing terrible challenges. There are many political, social, religious and economic pending issues. Poverty has been the order of the day. An average Nigerian live below red line. Mass unemployment in the country produces thug and fuels thuggery. Jobless youths see thuggery as more profitable than anything including education. Militancy spread everywhere. A country whose situation is this must be faced with grave security challenges and of course, this is exactly the true state of affairs in Nigeria. However, Islamic Heritage contains a rich tradition of high values and norms of behavior, which governs personal, professional and business life. This paper discusses the instrumentality of effective use of the Islamic panacea in tackling moral degeneration and insecurity that have both become the bane of Nigeria.